Systemic glucose-insulin-potassium reduces skeletal muscle injury, kidney injury, and pain in a murine ischaemia-reperfusion model - Daniel B. Buchalter; David J. Kirby; Utkarsh Anil; Sanjit R. Konda; Philipp Leucht (Bone & Joint Research, 2023)
Aims: Glucose-insulin-potassium (GIK) is protective following cardiac myocyte ischaemia-reperfusion (IR) injury, however the role of GIK in protecting skeletal muscle from IR injury has not been evaluated. Given the similar mechanisms by which cardiac and skeletal muscle sustain an IR injury, we hypothesized that GIK would similarly protect skeletal muscle viability. Methods: A total of 20 C57BL/6 male mice (10 control, 10 GIK) sustained a hindlimb IR injury using a 2.5-hour rubber band tourniquet. Immediately prior to tourniquet placement, a subcutaneous osmotic pump was placed which infused control mice with saline (0.9% sodium chloride) and treated mice with GIK (40% glucose, 50 U/l insulin, 80 mEq/L KCl, pH 4.5) at a rate of 16 µl/hr for 26.5 hours. At 24 hours following tourniquet removal, bilateral (tourniqueted and non-tourniqueted) gastrocnemius muscles were triphenyltetrazolium chloride (TTC)-stained to quantify percentage muscle viability. Bilateral peroneal muscles were used for gene expression analysis, serum creatinine and creatine kinase activity were measured, and a validated murine ethogram was used to quantify pain before euthanasia. Results: GIK treatment resulted in a significant protection of skeletal muscle with increased viability (GIK 22.07% (SD 15.48%)) compared to saline control (control 3.14% (SD 3.29%)) (p = 0.005). Additionally, GIK led to a statistically significant reduction in gene expression markers of cell death (CASP3, p < 0.001) and inflammation (NOS2, p < 0.001; IGF1, p = 0.007; IL-1β, p = 0.002; TNFα, p = 0.012), and a significant reduction in serum creatine kinase (p = 0.004) and creatinine (p < 0.001). GIK led to a significant reduction in IR-related pain (p = 0.030). Conclusion: Systemic GIK infusion during and after limb ischaemia protects murine skeletal muscle from cell death, kidneys from reperfusion metabolites, and reduces pain by reducing post-ischaemic inflammation. Cite this article: Bone Joint Res 2023;12(3):212–218.